Pendampingan Pengawasan Pembangunan Masjid Sheiik Mohideen Desa Payung Kecamatan Weleri Kabupaten Kendal - Firman, Annas; Kumalasari, Dwi; Wati, Tisna; Annasir, Malik; Rabbani, Nauval; Imawan, Adhe; Latifah, Evi (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2024)
Planning for mosque construction is based on local conditions by taking into account population structure and community procedures or patterns (SNI 03-1733-2004). However, not only in terms of planning, but in terms of supervising the implementation of mosque construction, experts are also needed who are familiar with building construction so that supervisors can direct construction workers in carrying out construction in accordance with planning documents. Construction of the Sheiik Mohideen Mosque on Jalan KH. Abdul Wahab RT. 001 RW. 002 Payung Village, Weleri District, Kendal Regency requires experts who are able to supervise the implementation of the construction of the Sheiik Mohideen Mosque so that the mosque that is built will be in accordance with the plans and wishes of the residents. Therefore, assistance in supervising the implementation of the construction of the Sheiik Mohideen mosque in Payung Village, Weleri District, Kendal Regency is needed, so that the mosque is built in accordance with the planning, the quality of the building is good, and the construction time is effective because the implementation of the mosque building is in accordance with the planning and produces a building of good quality. worthy. So the mosque construction committee collaborated with the service team from the Construction Engineering Study Program to provide assistance in supervising the construction of the Sheiik Mohideen Mosque. The methods used in this supervisory assistance include initial assistance, surveys, discussions and supervision. The result of this service activity is that the mosque has been built according to the planning and wishes of the residents with good quality and the right implementation time.